A New Method for Evaluating Compliance with Industry Self‐Regulation Codes Governing the Content of Alcohol Advertising. (17th May 2013) - Babor, Thomas F.; Xuan, Ziming; Damon, Donna
<x xml:space="preserve">Abstract</x> Background This study evaluated the use of a modified Delphi technique in combination with a previously developed alcohol advertising rating procedure to detect content violations in the U.S. Beer Institute Code. A related aim was to estimate the minimum number of raters needed to obtain reliable evaluations of code violations in television commercials. Methods Six alcohol ads selected for their likelihood of having code violations were rated by community and expert participants (N = 286). Quantitative rating scales were used to measure the content of alcohol advertisements based on alcohol industry self‐regulatory guidelines. The community group participants represented vulnerability characteristics that industry codes were designed to protect (e.g., age <21); experts represented various health‐related professions, including public health, human development, alcohol research, and mental health. Alcohol ads were rated on 2 occasions separated by 1 month. After completing Time 1 ratings, participants were randomized to receive feedback from 1 group or the other. Results Findings indicate that (i) ratings at Time 2 had generally reduced variance, suggesting greater consensus after feedback, (ii) feedback from the expert group was more influential than that of the community group in developing group consensus, (iii) the expert group found significantly fewer violations than the community group, (iv) experts representing different professional backgrounds did not differ among themselves in the number of violations identified, and (v) a rating panel composed of at least 15 raters is sufficient to obtain reliable estimates of code violations. Conclusions The Delphi technique facilitates consensus development around code violations in alcohol ad content and may enhance the ability of regulatory agencies to monitor the content of alcoholic beverage advertising when combined with psychometric‐based rating procedures.